Outcome of Neoadjuvant Intra-Arterial Chemotherapy and Radical Hysterectomy for Treatment of Bulky Stage IB to Stage IIB Uterine Cervical Cancer: Can Postoperative Irradiation Be Avoided? - Ujihira, Takafumi; Ota, Tsuyoshi; Kusunoki, Soshi; Sugimori, Yayoi; Kimura, Miki; Kaneda, Hiroshi; Terao, Yasuhisa; Ogishima, Daiki; Takeda, Satoru (International journal of gynecological cancer, 2016)
We evaluated whether our neoadjuvant intra-arterial chemotherapy (NAIC) effectively precludes the need for postoperative radiation therapy in patients treated by radical hysterectomy for IB2 to IIB cervical cancer. Study subjects were 52 patients with a bulky cervical tumor diagnosed and treated at Juntendo University Hospital or Juntendo Nerima Hospital. The NAIC combined cisplatin, epirubicin, mitomycin-C, and 5-fluorouracil; and radical hysterectomy was to be performed after 2 cycles. The main variables analyzed were clinical and histologic response to NAIC, NAIC-related adverse events, adjuvant chemotherapies, relapse-free and overall survival, recurrence, and prognostic factors. Patients were judged eligible for radical hysterectomy, and 51 underwent the surgery. The overall positive response (complete response [CR] + partial response [PR]) to NAIC was 88.5%. Median follow-up time was 84 months (5-136 months). Three-year relapse-free survival and overall survival were 80.5% and 77.8%, respectively. The recurrence rate was 19.2% (10/52 patients). Seven (13.5%) of the 52 patients died from the disease during follow-up. Lymph node status (positive vs negative) and the histologic effect of NAIC (grades 0-1 vs grades 2-3) were shown to be prognostic factors (P = 0.024 and P = 0.021, respectively). Our NAIC strategy seems to be well tolerated and beneficial for patients with bulky IB2 to IIB cervical cancer. With this strategy, radiation therapy remains an option in cases of recurrence. For cases in which lymph node metastasis is found or the histologic effect of NAIC is low, our adjuvant chemotherapy regimen may need adjustment to improve prognosis.